The effect of addition of hydroxyapatite from skipjack tuna (katsuwonus pelamis) fish bone flour to the transverse, impact, and tensile strength of heat cured acrylic resin - Diwya N. Hapsari; Sinta C. Wardani; Wahidatul A. Firdausya; Khoulah Amaturrohman; Hepy P. Wiratama (Journal of Dentomaxillofacial Science, 2020)
Objective:This study aims to determine the effect that occurs when heat cured acrylic resin is added hydroxyapatite which is synthesized from skipjack fish bones.Material and Methods: This study using 27 samples of heat cured acrylic resin for each mechanical strength divided into 3 groups, namely groups with the addition of 0%, 2%, and 5% hydroxyapatite from the weight of the polymer.Results: The analysis showed a significant decrease in transverse strength with 5% addition of hydroxyapatite group (One-way AnovaÂ test, p = 0.001), a significant decrease in impact strength occurred in both groups of 2% and 5% addition of hydroxyapatite (One-way Anova test, p = 0.000), and also the addition of 2% & 5% hydroxyapatite caused a significant decrease in tensile strength (One-way Anova test, p = 0.018).Conclusion: Hydroxyapatite synthesized from skipjack fish bone affects the mechanical strength of acrylic resins, namely transverse, impact and tensile.